Wear Behaviour of Crankshaft Journals Filled by Submerged Arc Welding - Öztürk, A.A.; Gülenç, B.; Durgutlu, A.; Kahraman, N. (Металлофизика и новейшие технологии, 2014)
In this study, wear behaviour of crankshaft journals filled by a submerged arc welding with different welding wires and powders is investigated. Hardness and microstructure variations in the submerged arc welding are examined. In addition, the amount of weight loss in abrasion samples of filling dry and lubrication ambience is measured under 40 N loads. It is observed that the amount of abrasion decreased with the increase of hardness at a certain point. Thin wire structure is provided for better abrasion resistance, and abrasion decreases with lubrication. В работе исследован режим износа цапф коленчатого вала, обработанных дуговой сваркой под флюсом с различными сварочными проволоками и порошками. Изучены вариации твёрдости и микроструктуры при дуговой сварке под флюсом. Кроме того, была измерена величина потери веса в образцах, подвергнутых истиранию в сухих и смазочных средах при нагрузках в 40 Н. Наблюдалось уменьшение величины истирания с увеличением твёрдости до определённого предела. Было обеспечено использование тонкой проволоки для лучшего сопротивления истиранию, а истирание уменьшалось при смазке. В роботі досліджено режим спрацювання цапф колінчастого валу, оброблених дуговим зварюванням під флюсом з різними зварювальними дротами і порошками. Досліджено варіації твердості та мікроструктури при дуговому зварюванні під флюсом. Крім цього, було виміряно величину втрати ваги в зразках, підданих стиранню в сухих і змащувальних середовищах при навантаженнях у 40 Н. Спостерігалося зменшення величини стирання зі збільшенням твердості до певної границі. Було забезпечено використання тонкого дроту для кращого опору стиранню, а стирання зменшувалося при змащуванні.